The Role of Agricultural Extension in Using Digital Transformation to Address Salinity Problems and Decreasing Water Resource Efficiency in the Al-Jabal Al-Akhdar Region - Libya. (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the role of digital transformation in enhancing the efficiency of agricultural extension to address soil salinity issues and the deterioration of water quality in the Al-Jabal Al-Akhdar region (Al-Marj, Tolmeita, Al-Bayda, Shahat, Sousa, and Derna). The study adopted a descriptive-analytical approach, collecting data through a questionnaire distributed to a random sample of 120 agricultural extension officers.The results indicated that extension officers possess a high level of knowledge regarding salinity symptoms, with a mean of 4.10. "Visual monitoring of salt crusts on the soil surface" ranked first with a mean of 4.55, followed by "drying and withering of leaf tips" with a mean of 4.48. However, the results revealed a gap in the use of advanced digital technologies (such as Geographic Information Systems (GIS) and Remote Sensing (RS)), where the mean decreased to 2.87. Meanwhile, current digital activity was limited to social media applications at a rate of 95.8%.The study also revealed "critical obstacles" hindering digital transformation, foremost among which was frequent power outages with a mean of 4.78 and an agreement rate of 98.3%, followed by poor internet connectivity with a mean of 4.65, and weak technical coordination between the central administration and field offices. Statistical analysis (coefficient of determination) proved that digital transformation contributes 58.1% to improving the efficiency of the extension system in facing water and soil crises.The study recommended adopting the concept of "Climate-Smart Agriculture" (CSA) and activating a procedural roadmap that includes: equipping extension offices with solar energy systems to overcome the electricity crisis, training personnel in spatial technologies (GIS and RS), and developing digital early warning platforms linked to the Ministry of Agriculture's databases to ensure rapid response to seawater intrusion and soil degradation
Keywords: Agricultural Extension, Digital Transformation, Soil Salinity, Water Resource Efficiency, Al-Jabal Al-Akhdar - Libya